Citizenship rights of immigrants in Portugal - Oliveira Daré, Geisa (2022)
International migrations are in the list of the political agenda of the countries, especially the developed ones, since they have experienced the growth of the immigrant population and the diversification of the countries of origin due to the effects of globalization. Under the humanitarian bias, the integration of immigrants in the respective host societies is necessary. However, the integration processes aren’t always satisfactory. One of the biases of integration is related to citizenship rights. Based on this, the article seeks to analyze the legal and political treatment of citizenship rights of immigrants in Portugal. There is a great effort on the part of the Portuguese government in the institution of organizations to deal with the issue affecting immigration. However, it is necessary to verify to what degree Portuguese legislation and actions are adequately addressing the process of integration of the immigrants.